1992
DOI: 10.1128/jcm.30.12.3117-3121.1992
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sporadic Campylobacter infections: results of a case-control study in southeastern Norway

Abstract: , a case-control study designed to identify risk factors for sporadic infections with thermotolerant Campylobacter bacteria was conducted in three counties in southeastern Norway. The investigation was confined to infections which were acquired in Norway. A total of 52 bacteriologically confirmed cases and 103 controls matched by age, sex, and geographic region were interviewed. The following risk factors were found to be independently associated with illness in conditional logistic regression analysis: consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
1
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(111 citation statements)
references
References 25 publications
3
104
1
3
Order By: Relevance
“…This reflects a continuous influx of contaminated runoff from the adjacent areas and a relatively low die-off rate of Campylobacter in water, which can explain water as an important reservoir for Campylobacter. Nondisinfected water is associated with Campylobacter infection both in broilers and humans, internationally as well as in Norway (Kapperud et al 1992(Kapperud et al , 1993Friedman et al 2000;Jones 2001;Sahin et al 2002;Herman et al 2003;Kapperud et al 2003), and water may constitute the common reservoir linking infection in humans and animals (Friedman et al 2000). Recent results indicating a symbiotic relationship between Campylobacter and aquatic amoebae may support this hypothesis (Axelsson-Olsson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects a continuous influx of contaminated runoff from the adjacent areas and a relatively low die-off rate of Campylobacter in water, which can explain water as an important reservoir for Campylobacter. Nondisinfected water is associated with Campylobacter infection both in broilers and humans, internationally as well as in Norway (Kapperud et al 1992(Kapperud et al , 1993Friedman et al 2000;Jones 2001;Sahin et al 2002;Herman et al 2003;Kapperud et al 2003), and water may constitute the common reservoir linking infection in humans and animals (Friedman et al 2000). Recent results indicating a symbiotic relationship between Campylobacter and aquatic amoebae may support this hypothesis (Axelsson-Olsson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similar tendencies on increasing incidences have been reported from other developed countries (Friedman et al 2000). Two case-control studies conducted in Norway, during 1989Norway, during -1990Norway, during and 1999Norway, during -2000, identified consumption of poultry meat purchased raw as a significant risk factor in regard to campylobacteriosis (Kapperud et al 1992(Kapperud et al , 2003. In order to reduce the prevalence of contaminated broiler meat at retail sale, minimizing the prevalence of positive flocks at farm level is considered as the most effective means (Phillips 1995;Altekruse et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…4,15 Household pets have also been implicated as a risk factor for human infections. 4,16,17,18 Dogs and cats are known to carry campylobacteria in their intestinal tracts without any ill effects, but Skirrow 7 considered that certain conditions such as stress and dietary change result in campylobacter enteritis. Some workers 19,20 concluded that C jejuni is probably not a primary pathogen in dogs and cats, and others [21][22][23] have reported the isolation of C upsaliensis from healthy domestic cats and dogs.…”
mentioning
confidence: 99%
“…Even after traditional slow chilling there is a significant decline of this agent (Chang et al, 2003). Accordingly, pig carcasses and pork are not regarded as an important source of Campylobacter in a public health context as confirmed by most epidemiological studies (Kapperud et al, 2003;Kapperud et al, 1992) and analysis by Domingues et al (2009). This conclusion is in contrast to Fosse et al (2008a) who ranked the Campylobacter as high risk, although lower than Y. enterocolitica.…”
Section: Final Low Risks Excluded From Further Considerationsmentioning
confidence: 99%
“…This was taken into account when applying the information in the final risk ranking. Low relevance due to the significant reduction seen after carcass chilling (in particular blast chilling, see section 2.3 for references) Kapperud et al, 1992;Kapperud et al, 2003;Fosse et al, 2008a;Pires et al, 2010 Clostridium botulinum 24 (combination of incidence data and expert opinion) Fosse et al, 2008a Low relevance, attribution reflects preserving practices in different EU countries, e.g. cases due to pork vary from 0% in Scandinavian countries or UK to over 80% in Poland Brett, 1999;Aureli et al, 1999;Kuusi et al, 1999;Galazka and Przybylska, 1999;McLauchlin and Grant, 2007 Clostridium difficile N/A Low relevance.…”
Section: Source Attributionmentioning
confidence: 99%